New data on distribution, morphology and ecology of Oedogonium capillare Kützing ex Hirn (Oedogoniales, Chlorophyta) in Poland - Marta, Pikosz; Beata, Messyasz (Biodiversity: Research and Conservation, 2016)
Algological investigations were focused on taxonomy, chorology and ecology of threatened filamentous green alga species in Poland. Studies on Oedogonium capillare Kützing ex Hirn growing in large quantities in association with Cladophora rivularis (Linnaeus) Hoek in pond were conducted. The aim of these studies was to describe the distribution, ecology and morphology of O. capillare as part of a more comprehensive study of this filamentous green alga. It is the eighth record in Poland for O. capillare. Filaments of O. capillare were grown over a wide pH range (7.3-9.6) and in high variability of nutrients. Vegetative cells, oogonia and antheridia were observed, which allowed taxonomic identification. O. capillare occurs in eutrophic waters which requires protection of its habitat.